The energy efficiency of the solar heating system with combined solar collector - Shapoval, Stepan (Lviv Polytechnic National University, 2015)
This article analyzes the influence of transparent coating on the efficiency of the combined solar collector. The prospects of solar heating systems’ usage, their main problems and their solutions are described. Heat of roofing material of the building was shown to be effectively used. The task is to increase the efficiency of the combined solar collector. The results of researches of the amount of solar radiation on the combined solar collector in the gravitational system of solar heating are described. The corrugated heat sink was shown to improve the efficiency of solar collector. The importance of the protection of solar collectors by the transparent coating was described. The matrix planning of three-factor experiment with interaction of factors was composed. The analytical and graphical dependences of the efficiency of the combined solar collector with a transparent coating and without it on the angles of incidence of the heat flux and its intensity were described. The changes in the effectiveness of the combined solar collector with transparent coating were shown. Проаналізовано вплив прозорого покриття на ефективність комбінованого геліоколектора. Описано перспективи використання систем сонячного теплопостачання, основні їхні проблеми та способи їх вирішення. Показано, що можна ефективно використовувати тепло покрівельного матеріалу будівлі. Поставлено завдання підвищити ефективність комбінованого геліоколектора. Описано результати досліджень надходження сонячного випромінювання на комбінований геліоколектор у гравітаційній системі сонячного теплопостачання. Показано, що гофрований теплопоглинач дає змогу підвищити ефективність геліоколектора. Описано важливість захисту геліоколекторів прозорим покриттям. Cкладено матрицю планування трифакторного експерименту із урахуванням взаємодії факторів. Відображено аналітичні та графічні залежності ефективності комбінованого геліоколектора з прозорим покриттям та без нього від кутів падіння теплового потоку та його інтенсивності. Показано, наскільки змінюється ефективність комбінованого геліоколектора під час покриття його прозорим захищенням.
Енергетична ефективність системи сонячного теплопостачання із комбінованим геліоколектором
Keywords: combined solar collector; transparent coating; the coefficient of efficiency; the heat flux; комбінований геліоколектор; прозоре покриття; коефіцієнт ефективності; тепловий потік